Macrophage colony-stimulating factor ameliorates myocardial injury in mice after myocardial infarction by regulating cardiac macrophages through the P2X7R/NLRP3/IL-1β signal pathway - Shu-Juan Zhang; Cong-Xin Huang; Qing-Yan Zhao; He Huang; Jian Zhang (Heliyon, 2023)
Aims: To investigate the effects of M-CSF on myocardial injury in mice after MI by regulating different types of cardiac macrophages through the P2X7R/NLRP3/IL-1β signal pathway. Methods: A total of 60 C57BL/6J WT mice were used, with the Sham Group subjected to ligation without ligation through the LAD, the MI model was prepared by ligation of the LAD in the MC Group and MM Group, with the M-CSF reagent (500 μg/kg/d) being given an intraperitoneal injection for the first 5 days after surgery in the MM Group. All mice were fed in a barrier environment for 1 week. After the study, myocardial tissues were collected and IL-4, IL-6, IL-10, TNF-α, MCP-1, IFN-α, ANP, BNP, β-MHC, Collage I, Collage III, P2X7R, NLRP3, IL-1β, Bax, Caspase 3, C-Casp 3, Bcl-2, M1/2 macrophage, the apoptosis of cardiomyocytes, and the collagen deposition were detected. Results: The inflammatory response was significantly lower in the MM Group, the cardiomyocyte apoptosis, fibrosis, and hypertrophy were inhibited compared to the MC Group, and the levels of P2X7R, NLRP3, and IL-1β were also statistically lower in the MM Group. Additionally, the expression of M2 macrophages increased in the MM Group while the M1 macrophages statistically decreased compared to the MC Group. Conclusion: M-CSF can significantly increase the expression of M2 macrophage and reduce the level of M1 macrophage by inhibiting the levels of NLRP3/IL-1β-related proteins, thereby inhibiting inflammation, ameliorating reducing myocardial hypertrophy, apoptosis, and fibrosis, improve myocardial injury in mice after MI.